2019
DOI: 10.1002/pc.25449
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously enhancing the thermal conductivity and dielectric constant of BN/CF hybrid filled polypropylene/polystyrene composites via in situ reactive processing

Abstract: Thermal conductive and electrical insulating polymer composites are exerted a tremendous fascination on the field of thermal management. The effective utilization of fillers is indispensable to construct the thermal conductive pathway to fabricate high thermal conductive polymer composites. Herein, a facile approach involves selective localization of boron nitride (BN) and carbon fiber (CF) through in situ polymerization of styrene through reactive processing as well as double‐percolation structure design. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The dielectric constants of cPBO-15 and cPBO-20 were higher than that of cPBO-10 due to their decreased porosity. All cPBO aerogels had a lower dielectric constant than that of other high-performance polymers such as polyimide, , polystyrene, polyaryletherketone, , and polysiloxane . Also, the dielectric losses of cPBO and P­( o AI-a) aerogels­(Figure b) were very small; most of them were less than 0.06.…”
Section: Resultsmentioning
confidence: 96%
“…The dielectric constants of cPBO-15 and cPBO-20 were higher than that of cPBO-10 due to their decreased porosity. All cPBO aerogels had a lower dielectric constant than that of other high-performance polymers such as polyimide, , polystyrene, polyaryletherketone, , and polysiloxane . Also, the dielectric losses of cPBO and P­( o AI-a) aerogels­(Figure b) were very small; most of them were less than 0.06.…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, the result can be concluded from the Table 2 that the T 5% and the T 50% were increased significantly compared with the PP70/PS30 blend, which indicated that the hybrid nanofillers had a nice enhancement on the thermal stability of the PP/PS blend. Jiang et al 35 investigated the stability of the BN/CF hybrid filled PP/PS composites. The result showed that higher thermal stability of BN/CF/PP/PS composites can be achieved, which was consistent with the result in this work.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of clay degraded the mechanical properties of the blends due to the poor adhesion between the OMC and the PP matrix. Jiang et al 35 prepared the BN/CF hybrid filled PP/PS composites via in‐situ reactive processing and studied the morphology and properties of the composites. The results showed that the BN and CF were selectively localized in PS phase, the thermal conductivity and dielectric constant of the composites improved obviously compared with that of composites prepared by simple melt blending technique.…”
Section: Introductionmentioning
confidence: 99%
“…Sangamesh et al 35 found that 1.5 wt% BN filled CF/epoxy resin (EP) showed the improvement of tensile modulus by 19.4% whereas the tensile strength improvement by 12.3% in comparison with those of unfilled composites. In addition, Jiang et al 36 showed that the thermal conductivity values was promoted from 0.22 W/(m·K) for polypropylene (PP)/polyethylene (PS) blends to 0.62 W/(m·K) with 14.5 wt% BN and 18 wt% CF. Obviously, the addition of h‐BN and CF will enhance the mechanical properties and thermal conductivity of the polymeric matrices.…”
Section: Introductionmentioning
confidence: 99%